KAJIAN MENGENAI AKTA NOTARIS TENTANG PENGANGKATAN ANAK YANG KEMUDIAN DISANGKAL OLEH SALAH SEORANG AHLI WARIS DIHUBUNGKAN DENGAN PEMBAGIAN HARTA WARISAN - NOVA ANDRIANI (PREMISE LAW JURNAL, 2016)
The conclusion of the research is that legal domicile of adopting a child in Indonesia has to have Notarial deed as it is stipulated in Article 10 Number 1 of Staatsblad No. 129/1917. In order to get justice for a valid heir, in the process of distribution of inheritance by foster parents to their adopted child in the Chinese community is that the adopted boy’s share is bigger than the biological girl’s although she is also a valid heir, but he can give part of his share to her as a gift. It is recommended that legal system of adopting a child in Indonesia should be reorganized systematically. Those who adopt a child should make a will before a Notary/PPAT (official empowered to draw up land deeds). Distributing inheritance in the Chinese community should follow a sense of justice by distributing inheritance equally between adopted child and biological child. Keywords: Adopting a Child, Notarial Deed, Inheritance